Antioxidant effects of Bifidobacterium longum T37a in mice weight loss and aging model induced by D-galactose - Wang, Ya; Wang, Jiahui; Li, Hehai; Lao, Jianlong; Jia, Dan; Liu, Junlong; Wang, Jinming; Luo, Jianxun; Guan, Guiquan; Yin, Hong; Li, Youquan (BMC microbiology, 2023)
Probiotics can reduce free radical scavenging rate and oxidative damage, and improve activity of crucial antioxidative enzymes in host cells. This study aimed to isolate Bifidobacterium spp. from faeces of babies, and investigate the antioxidant effects of the Bif. longum T37a in mice weight loss and aging model induced by D-galactose. T37a have good antioxidant properties in the DPPH assay and anti-lipid peroxidation test. Compared with the model group, T37a low group significantly increased the thymus index and the levels of T-AOC and GSH-Px of mice. T37a high group significantly decreased the spleen and liver index of mice and the levels of MDA in liver, significantly increased in liver HDL-C levels, and decreased LDL-C in liver. T37a may be an anti-aging and weight-loss probiotics for its antioxidant capacity, and it is necessary to study further the molecular mechanism of T37a as antioxidant.